Socio-psychological antecedents of pro-environmental intentions and behaviors among Iranian rural women: An integrative framework - Karimi, Saeid; Mohammadimehr, Sahra (Frontiers in Environmental Science, 2022)
The main purpose of this research was to identify factors influencing Iranian rural women’s pro-environmental intentions and behaviors by integrating the Theory of Planned Behavior and the Value-Belief-Norm theory into a theoretical framework. The model was tested using the partial least squares structural equation modeling (PLS-SEM) on data collected through a questionnaire survey from 332 Iranian rural women. The results indicated that the integrated model could account for 67 and 29 percent of the variance in pro-environmental intentions and behaviors, respectively. Perceived behavioral control was the strongest antecedent of pro-environmental behaviors, followed by intention. Perceived behavioral control was also the strongest direct determinant of intentions, followed by subjective norms and attitudes. In addition, the results revealed that awareness of consequences was indirectly and significantly related to intention through subjective norms, attitudes, and perceived behavioral control. Overall, the results provided a strong support for the integrative model and yielded more insight into socio-psychological factors influencing Iranian rural women’s pro-environmental intentions and behaviors. The empirical findings of this study can be used by researchers, policymakers, and governments to develop and implement effective programs to promote sustainable behaviors among rural women.